Implication of the 5-HT(2A) and 5-HT(2C) (but not 5HT(1A)) receptors located within the periaqueductal gray in the elevated plus-maze test-retest paradigm in mice - Gomes, K. S. [UNESP]; Nunes-De-Souza, R. L. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
A single exposure to the elevated plus-maze test (EPM) increases open arms avoidance and reduces or abolishes the anxiolytic-like effect of benzodiazepines assessed during a second trial, a phenomenon defined as "one-trial tolerance" (OTT). It has been emphasized that the dorsal portion of the midbrain periaqueductal gray (dPAG) plays a role on this enhanced aversion phenomenon in maze-experienced rodents. Given that intra-dPAG injections of a wide range of serotonergic 5-HT(1A), 5-HT(2A) and 5-HT(2C) receptor agonists produce anxiolytic-like effects in maze-naive rodents, the present study examined the effects of the 5-HT(1A) receptor agonist 8-OH-DPAT (5.6 and 10.0 nmol in 0.15 mu l) the preferential 5-HT(2A) receptor agonist DOI (2.0 and 8.0 nmol in 0.1 mu l) and the preferential 5-HT(2C) receptor agonist MK-212 (21.2 and 63.6 nmol in 0.1 mu l) microinjected into the dPAG prior to Trial 1 and Trial 2 on the behaviour of mice in the EPM. Test sessions were recorded and subsequently scored for anxiety-like behaviour (percentage of open arms entries and time) as well as general locomotor activity (closed arm entries). The results showed a lack of 8-OH-DPAT (5.6 and 10.0 nmol) effect on the behaviour of maze-naive and maze-experienced mice, while intra-dPAG microinfusions of DOI (8 nmol) reduced anxiety-like behaviour only in maze-experienced mice that had received a similar treatment prior to Trial 1. Furthermore, intra-dPAG MK-212 (63.6 nmol) showed an anxiolytic-like effect on both Trial I and Trial 2. Importantly, these effects were observed in the absence of any significant change in closed arm entries, the parameter considered to be a valid index of locomotor activity in the plus-maze. These results support the dPAG as a crucial structure involved in the neurobiology of the OTT phenomenon as well as accounting the role of the 5-HT(2A) and 5-HT(2C) receptors located within this midbrain structure on the emotional state induced by EPM test and retest paradigm mice. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: 5-HT(1A) and 5-HT(2A/2C) receptors; Elevated plus-maze; Mice; One-trial tolerance; Periaqueductal gray